O efeito do hidrograma e da concentração afluentes na remoção de material particulado em canal gramado - Moruzzi, Rodrigo Braga [UNESP]; Barbassa, Ademir Paceli; Shinzato, Alexandre (FapUNIFESP (SciELO), 2017)
The present work investigated the effect of hydrograph and inlet concentration on the removal of particle matter on a constructed real scale grassy channel. For this, three input hydrographs and initial concentration (Co) of particulate matter were investigated, as following: 65; 130; 195; 263, 327 and 400 mg/L, which were discharged in a grassy channel with 100 m length and a 2% slope. The peak of the hydrographs investigated was around 11±2 L/s; and the time base (tB), determined in the unloading point on the channel, ranged between 15, 25 and 35 minutes. The transit time in the channel (tT) was about 10.5±2.5 minutes, corresponding to a speed of 0.14±0.02 m/s. For 15 minutes tB, the average of maximum efficiencies was around 64±3% for the position 31±26 m. For 25 minutes tB, it was around 73±3% for 59±24 m. Finally, for 35 minutes tB the average of maximum efficiencies was about 65±3% for 73±15 m. It was verified that 70% of the values of the decay constant (kd) are between 0.005 and 0.015 s-1; and, when the tB of 15 minutes is not considered, 90% of the data is in the range of 0.005≤ kd ≤0.015 s-1. Also, a direct and proportional behavior of the final concentration (C*) and the initial concentration (Co) was identified.
The effect of hydrograph and of inlet concentration in particle removal on grassy channel
Keywords: Diffuse pollution; Grassy channel; Particulate matter; Phenomenological modeling; Urban drainage